2015
DOI: 10.1039/c5ta06202k
|View full text |Cite
|
Sign up to set email alerts
|

An integrated cobalt disulfide (CoS2) co-catalyst passivation layer on silicon microwires for photoelectrochemical hydrogen evolution

Abstract: Integrated cobalt disulfide (CoS2) co-catalyst passivation layer on Si microwires (MWs) were used as a photocathode for solar hydrogen evolution. Si MWs were prepared by photolithography and dry etching technique. The CoS2-Si photocathodes were subsequently prepared by chemical deposition and thermal sulfidation of the Co(OH)2 outer shell. The optimized onset potential and photocurrent of the CoS2-Si electrode were 0.248 V and −3.22 mA cm −2 (at 0 V), respectively. The best photocatalytic activity of the CoS2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 44 publications
7
60
1
Order By: Relevance
“…[41] The high-resolution N1sX PS peak appearing at 398.9 eV could be assigned to the presence of the mono-functional symmetrical nitrogen group on POP surface, supplying additional evidence for the formation of aC o-N x bond which is beneficial in improving electrocatalytic activity (Figure 6f). [42][43][44][45] The onset overpotential of the photocurrent of CoS x @POP film is approximately 92 mV versus RHE.T he photocurrentd ensity of the pristine Co 3 O 4 and CoS x is not high with the value of ca.À1.5 andÀ2.5 mA cm À2 at 0Vversus RHE, whichi sq uite similar to each other in terms of over potential. Similarly,t he positive displacement in the binding energies in the N1Ss pectrum of CoS x @POP compared with the bare POP demonstrated the interaction between the N-rich POP and cobalt sulfide nanoparticles which builds a" bridge"f or the charge transfer between POP and Co 9 S 8 (Figure 6f).…”
Section: Resultsmentioning
confidence: 96%
“…[41] The high-resolution N1sX PS peak appearing at 398.9 eV could be assigned to the presence of the mono-functional symmetrical nitrogen group on POP surface, supplying additional evidence for the formation of aC o-N x bond which is beneficial in improving electrocatalytic activity (Figure 6f). [42][43][44][45] The onset overpotential of the photocurrent of CoS x @POP film is approximately 92 mV versus RHE.T he photocurrentd ensity of the pristine Co 3 O 4 and CoS x is not high with the value of ca.À1.5 andÀ2.5 mA cm À2 at 0Vversus RHE, whichi sq uite similar to each other in terms of over potential. Similarly,t he positive displacement in the binding energies in the N1Ss pectrum of CoS x @POP compared with the bare POP demonstrated the interaction between the N-rich POP and cobalt sulfide nanoparticles which builds a" bridge"f or the charge transfer between POP and Co 9 S 8 (Figure 6f).…”
Section: Resultsmentioning
confidence: 96%
“…Pan et al constructed TiO 2 p-n homojunction to realize enhanced PEC H 2 evolution performance. Virtually, it is revealed that most of the excellent PEC water splitting cocatalysts are electrocatalysts, [18][19][20] such as transition metal dichalcogenides (TMDs), [21][22][23][24][25] phosphorous metal compounds, [26][27][28] metal oxides, [29][30][31][32] metal hydroxides, [29,33] etc. [16] Alternatively, engineering cocatalysts on the surface of photoelectrodes gradually came to sight recently, as the existence of cocatalysts can bring about the reduced overpotential, accelerated reaction kinetics, enriched active sites, and suppressed corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…The R ct1 signifies charge transfer resistance between PEDOT:PSS layer and the active material, whereas R ct2 refers to charge transfer resistance between the electrolyte and photoactive layer. 65 The resistive characteristics of the photocathodes are tabulated in Table S2. The solution resistance and R ct1 were found to be slightly different for different photocathodes.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%